CO2 conversion: the potential of porous-organic polymers (POPs) for catalytic CO2–epoxide insertion. Issue 19 (26th April 2016) - Alkordi, Mohamed H.; Weseliński, Łukasz J.; D'Elia, Valerio; Barman, Samir; Cadiau, Amandine; Hedhili, Mohamed N.; Cairns, Amy J.; AbdulHalim, Rasha G.; Basset, Jean-Marie; Eddaoudi, Mohamed
Abstract : New porous organic polymers have been synthesized and applied as catalysts for cycloaddition of CO2 and epoxides under mild conditions with excellent recyclability. Abstract : Novel porous organic polymers (POPs) have been synthesized using functionalized Cr and Co–salen complexes as molecular building blocks. The integration of metalosalen catalysts into the porous polymer backbone permits the successful utilization of the resultant functionalized material as a solid-state catalyst for CO2 –epoxide cycloaddition reactions with excellent catalytic performance under mild conditions of temperature and pressure. The catalysts proved to be fully recyclable and robust, thus showing the potential of POPs as smart functional materials for the heterogenization of key catalytic elements.